2009
DOI: 10.1111/j.1600-0528.2009.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits for dental care of nontraumatic origin

Abstract: ED visits for dental problems of nontraumatic origin are not insignificant. Over the study period, these visits were greater than for diabetes and hypertensive diseases. Policy efforts are needed to provide alternative options for seeking emergency dental care in Ontario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 10 publications
5
106
1
1
Order By: Relevance
“…10 In BC, 12 357 non-traumatic dental visits were made to ERs in 2013-2014 (268/100 000 people), with patients between the ages of 1 and 113 years somewhat evenly distributed in terms of gender, including multiple visits by the same patient over that same fiscal year. 7 The majority of the ER visits (70%) in BC for non-traumatic dental conditions consisted of working-age adults between the ages of 20 and 64 years with a common complaint related to non-urgent ‡ and preventable diseases, including dental and periapical abscesses (22.7%), toothache (18.1%) and dental caries (8.8%), 7 as found by Quiñonez and colleagues 6 and others 11 ; 70% of these visits were identified as non-urgent. The majority (98%) of these non-urgent dental patients were seen and discharged within a two-hour average time frame (e.g., the amount of time it takes between entering the ER for registration and being discharged or admitted to a hospital bed).…”
Section: Use Of Cihi Data Related To British Columbia Er Visitsmentioning
confidence: 73%
See 1 more Smart Citation
“…10 In BC, 12 357 non-traumatic dental visits were made to ERs in 2013-2014 (268/100 000 people), with patients between the ages of 1 and 113 years somewhat evenly distributed in terms of gender, including multiple visits by the same patient over that same fiscal year. 7 The majority of the ER visits (70%) in BC for non-traumatic dental conditions consisted of working-age adults between the ages of 20 and 64 years with a common complaint related to non-urgent ‡ and preventable diseases, including dental and periapical abscesses (22.7%), toothache (18.1%) and dental caries (8.8%), 7 as found by Quiñonez and colleagues 6 and others 11 ; 70% of these visits were identified as non-urgent. The majority (98%) of these non-urgent dental patients were seen and discharged within a two-hour average time frame (e.g., the amount of time it takes between entering the ER for registration and being discharged or admitted to a hospital bed).…”
Section: Use Of Cihi Data Related To British Columbia Er Visitsmentioning
confidence: 73%
“…[3][4][5] Low-income Canadians remain at greater risk for oral diseases and may rely on emergency rooms (ERs) to seek pain relief, placing an extra burden on the already over-stretched Canadian health care system. 6 Despite representing about 1% of the 16 million visits* made to ERs across Canada every year and not more than 1% of the $1.8 billion that these visits cost to Canadians, 7 we argue that these percentages are an underestimation of the actual impact for the health care expenditures as a whole.…”
Section: Entistry Remains Mostly Privately Financed Administeredmentioning
confidence: 87%
“…6 National-level data in the United States suggest that, over a 10-year period, ED visits for NTDC increased and at a faster rate than for all ED visits combined. 7 Yet, in Canada, most studies on ED visits for NTDC present data for only one or two years; 4,5 only one has presented trend data, but it was limited to homeless adults over a four-year period in one Ontario municipality. 3 Trend data are important, as they give researchers and policy-makers the ability to explore patterns in a given outcome, and allow for hypothesis formulation on potential environmental exposures and their effects on such trends.…”
mentioning
confidence: 99%
“…Further, though most studies on ED visits for NTDC in Canada quantify the burden, they do not report on the predictors of such visits either at the individual or area-based level. 4,5 What is known has relied on data on self-reported ED visits for NTDC in Canada, and suggests that cost barriers to dental care, oral pain, and bed days due to dental problems are predictors of such visits. 8,9 As a result of the above, this study aims to assess trends in ED visits for NTDCs in Ontario from 2006 to 2014, and to explore socio-demographic and geographic predictors of such visits.…”
mentioning
confidence: 99%
“…5 Studies have shown that most emergency visits result from dental decay. [6][7][8] Due to the described signs and symptoms, the emergency visits can Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
mentioning
confidence: 99%